Miners Federation of Great Britain statement on owners proposal, 27 April 1926 (page 1)
1926-04-27 "Miners Federation of Great Britain statement on owners proposal, 27 April 1926 (page 1)" [g0439001.jpg], 27 April 1926, Miners' Federation of Great Britain The Build Up